(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article discusses the theory of adult education (andragogy) and the importance of competency-based education in the medical field. Adult learning is characterized by learners’ experience, independence, and orientation toward practical application. The competency-based approach focuses not only on theoretical knowledge but also on professional skills, communication, clinical reasoning, and ethical responsibility. The study highlights the concept of human-centered medical care, where the patient’s needs, values, and safety are considered priorities. This approach contributes to the development of healthcare professionals’ competencies, promotes effective cooperation with patients, and improves the overall quality of medical services.